Differentiation of Brachyspira spp. isolated from laying hens using PCR-based methods and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. (July 2018) - Harms, Monika; Schmidt, Volker; Heydel, Tilo; Hauptmann, Jutta; Ahlers, Christine; Bergmann, Rene; Baums, Christoph G.
Avian intestinal spirochetosis (AIS), an important but neglected disease in laying hens, is caused by Brachyspira pilosicoli, B. intermedia, and B. alvinipulli . Poultry are also frequently colonized by putatively nonpathogenic species such as B. murdochii and B. innocens . We evaluated the differentiation of Brachyspira species by 3 methods: sequencing of the reduced nicotinamide adenine dinucleotide (NADH) oxidase gene ( nox ), matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), and a new multiplex (m)PCR targeting genes such as the tryptophanase A gene ( tnaA ) and the p-aminobenzoyl-glutamate hydrolase subunit B gene ( abgB ). Sequencing of 414 bp of the nox PCR amplification products generated from 41 pure cultures of avian Brachyspira isolates allowed presumptive species identification in 33 isolates with at least 99% identity in basic local alignment search tool analysis, including B. pilosicoli, B. intermedia, B. murdochii, B. innocens, and " B. pulli ". MALDI-TOF MS analysis was found to be a reliable tool for differentiation after extension of the manufacturer's database. In the mPCR, all isolates identified as B. pilosicoli and B. intermedia were positive for abgB and tnaA, respectively. The mPCR might be very useful in detecting Brachyspira species in mixed cultures including not only nonpathogenic species, such as B. innocens, but also one of the AIS pathogens. We found that MALDI-TOF MS analysis combined with the mPCR targeting tnaA and abgB was suitable for the identification of avian isolates of B. pilosicoli and B. intermedia, 2 important agents of AIS.